Characteristics of functional tension of qualified skiers when passing rises of different difficulty - Khmelnytska, J. K.; Filippov, M. M. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2015)
Purpose: studying of main functional changes in organism of qualified female skiers when passing rises of different difficulty.